Finite nondispersible groups all subgroups of which with nonprimary index are metacyclic - Zuzuk, L. I. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We describe the structure of finite nondispersible groups all subgroups of which with nonprimary index are metacyclic.